Introducing a book: Water Management (Resources and utilization) (آب و توسعه پایدار)
The book "Water Management" is the result of ten years of efforts of a motivated and tireless team that tried to tell about the necessity of adopting new approaches and paying attention to new topics in the country's water management through the scientific study of the components of water resource and consumption management.